Data Integration for Large-Scale Models of Species Distributions - Isaac, N.J.B.; Jarzyna, M.A.; Keil, P.; Dambly, L.I.; Boersch-Supan, P.H.; Browning, E.; Freeman, S.N.; Golding, Nick; Guillera-Arroita, G.; Henrys, P.A.; Jarvis, S.; Lahoz-Monfort, J.; et al. (ELSEVIER SCIENCE LONDON, 2020)
With the expansion in the quantity and types of biodiversity data being collected, there is a need to find ways to combine these different sources to provide cohesive summaries of species’ potential and realized distributions in space and time. Recently, model-based data integration has emerged as a means to achieve this by combining datasets in ways that retain the strengths of each. We describe a flexible approach to data integration using point process models, which provide a convenient way to translate across ecological currencies. We highlight recent examples of large-scale ecological models based on data integration and outline the conceptual and technical challenges and opportunities that arise.